Iowa Birdline update, August 28, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for August 28, 1989. Highlights include the continued presence of a Laughing Gull and a lot of Warbler movement. Epson - sheet feed/flatbed